Studying the effect of donor kidney volume ratios to recipients' body surface area, body mass index, and total body weight on post-transplant graft function. - Mahdavi, Arash; Negarestani, Amir Masoud; Masoumi, Navid; Ansari, Roya; Salem, Pegah; Dahesh, Tania; Mahdavi, Ali (Abdominal Radiology, 2023)
Objectives: The goal of this study was to retrospectively investigate the relationship between renal transplanted volume indexes (Total kidney volume (TKV)/Body surface area (BSA), Renal parenchymal volume (RPV)/BSA, Renal cortical volume (RCV)/BSA, RPV/Body mass index (BMI), RCV/BMI, RPV/Weight, RCV/Weight), and short- and long-term function of the graft. Methods: One-hundred and twelve live donor-recipient pairs from 2017 to 2018, whose donors underwent preoperative renal computed tomography angiography and recipients survived during 12 months of follow-up, were included in this study. Results: The crude and adjusted linear regressions for the effect of volume measurements by voxel and ellipsoid methods on the estimated glomerular filtration rate (eGFR) at different post-transplantation times demonstrated that the RPV/weight ratio had the most substantial crude effect on the eGFR 12 months and 4 years after renal transplant. Receiver operating characteristic (ROC) curves for six different renal volume ratios demonstrated no significant difference between these ratios in terms of discriminative ability (p value < 0.05). A strong direct correlation between TKV calculated by the ellipsoid formula with RPV and RCV measured using OsiriX software was noted. Analysis of ROC curves for renal volume indices has demonstrated fair to good discriminative ability of our cut-off points to estimate 4-year post-transplantation eGFR > 60 mL/min. Conclusion: Renal transplant recipients' volume indices, such as RPV/weight, had strong correlations with eGFR at different points in time, and renal transplant recipients with the volume ratios higher than our cut-off points had a good chance of having a 4-year post-transplantation eGFR higher than 60 mL/min.